Evaluation on Satisfaction and Oral impacts on daily performances of elderly at Nongbunmak, NakornRatchasima Province. - ทับทอง, ชัยรัตน์ (Thai Dental Public Health Journal, 2015)
The objective of this study was to assess satisfaction and oral impacts on daily performances of elderly, after wearing dental prosthesis at Nongbunmak Hospital during October 2012 – September 2013. Data were collected by interviewed fifty-six elderlyduring 24 June- 4 July 2014. Tool for assessment used the satisfaction and oral impacts on daily performances index form. Results showed that the elderly were male 62.5 percent and female 37.5 percent. Overview 83.9 percent of elderly had satisfaction to services and dental prosthesis. The most was a screening and registration (96.4 %). The second was a standard of the process (89.3 %). The un-satisfactionwere a process of oral health preparation (5.4 %)and a process of problem solving (3.6 %). 55.4 percent of elderly were not affectedin oral impacts on daily performances. The average OIDP Score was 4.76. The activity most affected on daily performances were eating (44.6 %)and speaking (28.6 %).